Bedside Neonatal Intensive Care Unit Correction of Congenital Diaphragmatic Hernia: Is Repair without Compromise? - Altokhais, Tariq; Soomro, Mohammad Aqil; Gado, Abdulmonem; Albassam, Abdulrahman (American Journal of Perinatology, 2016)
Objectives This study aims to evaluate the feasibility, safety, limitations, and outcomes of performing different surgical approaches and techniques for the bedside repair of congenital diaphragmatic hernia (CDH) in critically ill patients who cannot be transferred to the operating room.Study Design Between December 1997 and July 2013, medical charts of all neonates operated on at the bedside for CDH while on high-frequency oscillatory ventilation (HFOV) and nitric oxide were reviewed. Demographic data; contributing antenatal, perinatal, and postnatal factors; clinical presentation; associated anomalies; respiratory and hemodynamic status; operative details; complications, and outcome were analyzed.Results A total of 101 cases of CDH were operated on, of which 11 were in very critical condition and operated on at the bedside in the neonatal intensive care unit (NICU). The mean gestational age was 38.09 weeks, birth weight, 2.91 kg, and age at surgery, 10 days. All were on HFOV and inotropic support and had pulmonary hypertension. Nine of them were on nitric oxide. Mean preoperative parameters were as follows: O2, 52%; mean airway pressure, 15; pH, 7.40; Po2, 88.5 mm Hg; and Pco2, 47 mm Hg. Nine patients underwent laparotomy and two underwent thoracoscopy. All procedures were completed uneventfully.Conclusions Bedside repair of CDH in the NICU while on HFOV is feasible and safe. It is not associated with any compromise in the surgical approach or technique.
Keywords: congenital diaphragmatic hernia; bedside repair; neonatal intensive care unit; surgery; critically ill